Family Life Experiences in Caring for Children with Leukemia: A Literature Review - Siti Nurjanah; Yurike Septianingrum; Ratna Yunita Sari (Universitas Aisyah Pringsewu, 2022)
Acute Lymphoblastic Leukemia (ALL) is the most common childhood cancer, and ALL is the leading cause of death in children. Chronic diseases, one of which is cancer suffered by children, can provide varied responses to families. Caring for children with cancer requires a very long and complex process, so it requires good coordination between children, parents, families and the health team. The purpose of this literature review is to obtain in-depth information on the experiences of parents in caring for children with cancer. The method of writing this article is a literature review of 40 articles with the year 2019-2021 published from an electronic database, namely CINAHL, Web of Science, SAGE and Proquest. The method of searching and selecting articles used The Center for Review and Dissemination and the Joanna Briggs Institute Guideline and PRISMA diagram. Checklist with selection criteria using the PICOS approach. The results of a literature review show that while caring for children with cancer, parents experience stress, anxiety about losing a child, uncertainty in child treatment, difficulties in caring for children and family responsibilities. Support in the form of psychosocial, material, and social support is needed for the family. The declining health condition of children is the biggest obstacle for parents, material needs are needed to support the care of children suffering from cancer, and there is hope from parents for their child's recovery. Abstrak: Leukemia Limfoblastik Akut (LLA) adalah kanker anak yang paling umum, dan LLA adalah penyebab utama kematian pada anak-anak. Penyakit kronis salah satunya kanker yang diderita anak dapat memberikan respon yang bervariasi pada keluarga. Merawat anak penderita kanker membutuhkan proses yang sangat panjang dan kompleks, sehingga membutuhkan koordinasi yang baik antara anak, orang tua, keluarga dan tim kesehatan. Tujuan dari literature review ini adalah untuk mendapatkan informasi yang mendalam tentang pengalaman orang tua dalam merawat anak penderita kanker. Metode penulisan artikel ini adalah literature review sebanyak 40 artikel dengan tahun 2019-2021 yang diterbitkan dari database elektronik yaitu CINAHL, Web of Science, SAGE dan Proquest. Metode pencarian dan pemilihan artikel menggunakan The Center for Review and Dissemination dan Joanna Briggs Institute Guideline dan diagram PRISMA. Checklist dengan kriteria seleksi menggunakan pendekatan PICOS. Hasil studi pustaka menunjukkan bahwa selama mengasuh anak penderita kanker, orang tua mengalami stres, kecemasan kehilangan anak, ketidakpastian dalam perawatan anak, kesulitan dalam mengasuh anak dan tanggung jawab keluarga. Dukungan berupa psikososial, materil, dan sosial. dukungan diperlukan untuk keluarga. Kondisi kesehatan anak yang menurun menjadi kendala terbesar bagi orang tua, kebutuhan materi yang diperlukan untuk mendukung perawatan anak penderita kanker, dan ada harapan dari orang tua untuk kesembuhan anaknya.